SISTEM INFORMASI MANAJEMEN PADA HULUBALANG CULTURE CAFE BERBASIS WEB - Dona Dona; Urfi Utami; Kiki Yasdomi; Mi’rajul Rifqi; Khairul Sabri; Hendri Maradona; Nurvita Chandra (RJOCS (Riau Journal of Computer Science), 2026)
Hulubalang Culture Cafe in Ujungbatu that operating since 2017 faces ordering queues, transcription errors, and long waiting times as visits grow. The current process relies on waiter to customer interaction and printed menus, and sales are not systematically recorded, hindering daily, monthly, and yearly profit assessment. This study aims to design and develop an integrated, web based food and beverage ordering system that improves service efficiency and data accuracy while providing periodic sales reports for managerial decisions. The proposed solution implements an E-Menu accessed by scanning a QR Code at each table, the QR codes are generated using QR Code Generator and linked to dynamic menu pages with a cart flow and order confirmation step before tickets are sent to the kitchen. A structured development approach and black-box testing were applied. Results show a working system with menu, ordering, real-time order status, and automatic sales recaps operate as intended. the system also produces daily, monthly, and annual reports and supports per table unique QR codes.